ANALISIS VOLUME PERDAGANGAN DAN ABNORMAL RETURN SEBELUM DAN SESUDAH STOCK SPLIT PADA PERUSAHAAN BERTUMBUH DAN TIDAK BERTUMBUH - Ida Rohyani; Evaliati Amaniyah; Echsan Gani (Eco-Entrepreneur, 2016)
The purpose of this study is to obtain empirical evidance about the differences of stock trading volume and average abnormal return on growing and not growing company before and after stock split.  Based on purposive sampling, there are 38 sample. This study uses analysis of Wilcoxon Signed Test and Mann Whitney by the period of event is 31 days; 15 days before stock split (t-15) and 15 days after stock split (t+15). The result of study shows that there is no trading volume significance differences before and after stock split on growing and not growing company. The insignificance differences is also found in Average Abnormal Return before and after stock split on on growing and not growing company. Furthermore, there is no differences of trading volume and average abnormal return on on growing and not growing company before and after stock split.